Drag of road cars: cost-effective CFD setup, proposal of an aerodynamic concept and case studies - Soares, Renan Francisco (2015)
This research investigates the drag in automotive aerodynamics. The main aim is to maximize the fuel efficiency of road cars, mainly those produced in Brazil. This is believed to be possible by means of aerodynamic development in drag reduction. In order to achieve this aim, this research investigates starting from the computational solution of vehicle aerodynamics, an aerodynamic concept is proposed and some cases are investigated. Regarding the computational solution, this research outlines a best practice for the best costefficiency of computational resources, from the point of drag prediction over realistic car geometries. It may lead to improve the current aerodynamic development time in the automotive industry. As consequence, the increase in the amount of results would ground new concepts and shape optimization in a shorter time. The proposal of an aerodynamic concept for fastback car models is aligned to the drag reduction, and subsequently the fuel efficiency aspect. Even though it is a concept, it has been based on a systematic CFD (Computational Fluid Dynamics) analysis of blowing and suction jet methods. In addition, it also would be feasible in the view of manufacturing process. The third part of this work analyses the Brazilian Hatch 2015 cars and investigates the effect of exhaust gases on the drag coefficient of a realistic car model. The former compares the aerodynamic forces and geometry features of the best-selling Hatch 2015 car profiles, while the latter part deals with the quantitative effect of tailpipe position on the drag of a car model.